Automatic Rubber Tapping Bowl Cover Based on Raindrop Sensor and Remote-Control using Telegram - Dasmen, Rahmat Novrianda; Ardianto, Ardianto; Herda, Fitria Destian; Faizal, Faizal; Rasmila, Rasmila (Jurnal Listrik, Instrumentasi, dan Elektronika Terapan, 2026)
Rubber plantations are one of the primary commodities providing livelihoods for farmers in Indonesia, such as in South Sumatra Province. The main issue: rainwater contamination reduces the quality and market value of latex, impacting farmers’ income. The quality of the latex produced significantly affects its market value, with rainwater contamination being a key factor. A decline in latex quality will lead to a decrease in its market value, which in turn will affect rubber farmers’ income. Therefore, this study developed an IoT device for rubber tapping containers with a cover, which will automatically close the container using a rain sensor. Method action research with field testing in Meranjat Village, Ogan Ilir. This is an effort to prevent latex from being contaminated by rainwater during rainy weather conditions. The application and testing of this automatic rubber tapping container cover were conducted at a rubber plantation in Meranjat Village, Ogan Ilir Regency. Results: 95% closure success rate (sensor activates at 3–5 drops), PIR detection <30 cm, Telegram control. Test results show an automatic closure success rate of 95%, with the rain sensor activating after 3–5 drops of water. Additionally, this IoT device is equipped with a PIR sensor to alert users of any unauthorized entry or attempts to steal latex from the rubber tapping container. The PIR sensor can detect movement at a distance of less than 30 cm and activate an alarm as a warning. Furthermore, this study also added a remote-control feature for this IoT device using the Telegram app.